PELATIHAN COPYWRITING DAN DIGITAL MARKETING PADA PELAKU UMKM SENTRA USAHA DI KELURAHAN BUAH BATU KOTA BANDUNG - Yogi Muhammad Yusuf; Vikry Abdullah Rahiem; Charisma Asri Fitrananda (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2022)
Micro, Small and Medium Enterprises or commonly called UMKM are business activities or businesses run by individuals, households or small business entities. Based on a Bank Indonesia survey, 87.5 percent of UMKM were affected by the Covid-19 pandemic. Of this amount, around 93.2 percent of them were negatively affected on the sales side. With this background, the team conducted copywriting training and training related to digital marketing at one of the UMKM Business Centers in Bojongsoang District, Buah Batu Village, Bandung City. This service is carried out to increase sales by utilizing digital platforms. The ability to write in the media market place is very important to create a brand awareness effect on potential consumers. The problem is that partners have not been able to create captions, taglines, descriptions for products that will be stored in the marketplace storefront. In addition, related to digital marketing planning, the service team brought students to provide material according to what was learned in lectures. This service activity uses a contextual approach method, namely providing theoretical material first and followed by guidance and assistance to partners in making copywriting and digital marketing planning techniques. Then proceed with the facilitation method in creating content that can be uploaded directly on the marketplace or on their social media